The Effect of Using Electronic Educational Technology «Video Technology» on Learning Dribblings in Basketball - Mouloud Kenioua; Hocine Berkat (Lesya Ukrainka Volyn National University, 2021)
Topicality. The video technology become one of the modern electronic learning methods used in the field of physical education and sports Research Purpose.The current study aimed to use video technology as one of the modern educational methods and the extent of its impact on learning and acquiring the skill of dribbling in basketball among intermediate school students. Methods. The participants of the main study consisted of 26 students from an intermediate education institution. Measurement tools can be divided into two parts, the first is the scientific research tools such as personal interviews with experts, tests, questionnaire form for determining the most appropriate test to assess the skilful performance of dribbling, a test for evaluating the skill of dribbling and scientific observation. The second is the means and devices used that included: a laptop computer, a visual display device, a device for measuring height and weight, in addition to sports supplies and video tapes. Research Result. The results of the current study showed that the educational program followed influenced the development of students 'dribbling skill in basketball. The use of video technology enhanced learning the skill of dribbling in basketball among students. Conclusion. It has become necessary to use video tapes and various new electronic techniques such as includes virtual reality (VR), augmented reality (AR) in the physical education lesson, because of their importance in the learning process, and link the sense of hearing and sight in order to gain time and effort, and enhance the motivation of students.